Flowers Beads Bracelet’s - Dinda Widya Kumala; Feriadi Feriadi; Tina Safira; Muhammad Yasin (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
Handicraft in the form of flower bead bracelets (Flowers Beads Bracelet's) is a creative product that combines aesthetic elements and manual skills in one functional work of art. This bracelet is not only used as a fashion accessory, but also represents artistic and cultural values ​​in every detail of its design. This research or project aims to explore the manufacturing process, material selection, bead assembly techniques, and the potential selling value of the bracelet in the context of the creative industry. The results show that the design of flower bracelets made of beads has high visual appeal, is flexible to fashion trends, and can be developed as a superior product of craft-based MSMEs. In addition, the use of digital media in promotion also encourages the competitiveness of this product in both local and global markets.